Molecular Engineering of CoII Porphyrins with Asymmetric Architecture for Improved Electrochemical CO2 Reduction. Issue 8 (16th March 2022) - Bao, Wenwen; Huang, Senhe; Tranca, Diana; Feng, Boxu; Qiu, Feng; Rodríguez‐Hernández, Fermín; Ke, Changchun; Han, Sheng; Zhuang, Xiaodong
Abstract: The electrochemical reduction of carbon dioxide (CO2 ) based on molecular catalysts has attracted more attention, owing to their well‐defined active sites and rational structural design. Metal porphyrins (PorMs) have the extended π‐conjugated backbone with different transition metals, endowing them with unique CO2 reduction properties. However, few works focus on the investigation of symmetric architecture of PorMs as well as their aggregation behavior to CO2 reduction. In this work, a series of Co II porphyrins (PorCos) with symmetric and asymmetric substituents were used as model of molecular catalysts for CO2 reduction. Owing to the electron donating effect of 2, 6‐dimethylbenzene (DMB), bandgaps of the complexes became narrower with the increasing number of DMB. As electrocatalysts, all PorCos exhibited promising electrocatalytic CO2 reduction performance. Among the three molecules, asymmetric Co II porphyrin ( as ‐PorCo) showed the lowest onset potential of −288 mV and faradaic efficiencies exceeding 93 % at −0.6 V vs. reversible hydrogen electrode, which is highly competitive among the reported state‐of‐art porphyrin‐based electrocatalysts. The CO2 reduction performance depended on π‐π stacking between PorCo with carbon nanotubes (CNTs) and adjacent PorCos, which could be readily controlled by atomically positioned DMB in PorCo. Density functional theory calculations also suggested that the charge density between PorCo and CNT was highest due to the weak steric hindrance in as ‐PorCo, providing the new insight into molecular design of catalysts for efficient electrochemical CO2 reduction. Abstract : Beauty in balanced asymmetry : An asymmetric Co II porphyrin ( as ‐PorCo) is constructed with a substituent of 2, 6‐dimethylbenzene to enhance the charge transfer capability from carbon nanotubes to as ‐PorCo, resulting in large partial current density of 8 mA cm −2 and high turnover frequency of 5656 h −1 at −0.7 V vs. reversible hydrogen electrode in aqueous solution. The present study provides the new insight into molecular design of catalysts for efficient electrochemical CO2 reduction.